Modern Rhodium‐Catalyzed Organic Reactions 2005
DOI: 10.1002/3527604693.ch7
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium(I)‐Catalyzed Cycloisomerization and Cyclotrimerization Reactions

Abstract: IntroductionHighly efficient catalytic processes for the synthesis of natural and unnatural compounds of medicinal interest or functional materials play a central role in modern organic synthesis. The transformation of simple starting materials into monocyclic, bicyclic, and polycyclic scaffolds using transition metal-catalyzed cyclization reactions is one of the most powerful approaches to such methodology. Among the transition metal catalysts used in these reactions, rhodium complexes are particularly import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(16 citation statements)
references
References 41 publications
(63 reference statements)
0
15
0
Order By: Relevance
“…9 We hypothesized that a rhodium-catalysed cycloaromatisation reaction could be realized by harnessing the well-known oxidative cyclization process observed in Rh-catalysed 1,6-enyne reactions (Scheme 1c). [10][11][12][13][14][15][16] The triple bond of an enediyne opens up the possibility of forming a cyclic vinyl-rhodium species A via oxidative cyclization of ene-diyne 1-Rh. Isomerization of the oxidative cyclization product A should form Bproviding a direct route to the intriguing allenyl-rhodium intermediate B and an alternative route to a cyclic allene cf.…”
Section: Introductionmentioning
confidence: 99%
“…9 We hypothesized that a rhodium-catalysed cycloaromatisation reaction could be realized by harnessing the well-known oxidative cyclization process observed in Rh-catalysed 1,6-enyne reactions (Scheme 1c). [10][11][12][13][14][15][16] The triple bond of an enediyne opens up the possibility of forming a cyclic vinyl-rhodium species A via oxidative cyclization of ene-diyne 1-Rh. Isomerization of the oxidative cyclization product A should form Bproviding a direct route to the intriguing allenyl-rhodium intermediate B and an alternative route to a cyclic allene cf.…”
Section: Introductionmentioning
confidence: 99%
“…The transition-metal-catalyzed asymmetric [2 + 2 + 2] cycloaddition of α,ω-diynes with alkenes is one of the most convenient methods for the synthesis of chiral bicyclic 1,3-cyclohexadienes. In this transformation, the use of 1,2-disubstituted cyclic alkenes is capable of affording the corresponding chiral multicyclic 1,3-cyclohexadienes. , As such, our research group recently reported that the cationic rhodium­(I)/( R )-Difluorphos complex-catalyzed asymmetric [2 + 2 + 2] cycloaddition of α,ω-diynes 1 with indene ( 2a ) affords the corresponding tetracyclic 1,3-cyclohexadienes 3a in high yields with high regio- and enantioselectivity under mild conditions (Scheme , top) . In this reaction, enantioselectivity highly depended on the structures of α,ω-diynes 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Transition metal-catalyzed silylcarbocyclization is an established synthetic protocol for the construction of various ring systems containing silyl groups, in which the carbometalation initiated by the silylation of unsaturated motifs, such as alkynes and alkenes, is a key step . Silylcarbocyclization was first documented in Tamao’s report, where a nickel complex catalyzed the reaction of 1,7-diynes with hydrosilanes to give 1,2-dialkylidenecyclohexanes .…”
Section: Introductionmentioning
confidence: 99%